Urgensitas Amr Nahy Dalam Memahami Ayat-Ayat Al Qur’an - Siti Fahimah (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2018)
The Qur'an as well as the word of Allah revealed to the Prophet Muhammad has given birth to the community of readers. They try to understand and articulate the value of the Qur'an in the arena of life, until finally formed the fact of Islam. This can not be avoided from the activities of interpretation, understanding and contemplation of the meaning contained in the Qur'an. Activity understanding/interpretation of the Qur'an required a rule-order to avoid the wrong meaning, because in the Qur'an many we encounter mu'jizat Al Qur'an of which is about language. The language of the Qur'an differs from the language of modern law, for the legislation of the Qur'an is not limited to the love, its prohibitions and its legal consequences, but often coupled with the moral appeal to arouse individual consciousness. This appeal may take the form of persuasion, or it is about the advantages and disadvantages that can be gained by exercising or abandoning a command or threat of retribution/punishment in the Hereafter. Modern laws are often without such an appeal, as it is usually limited to an explanation of the terms to be followed and the unreal consequences of the law.